The Use of Folktale to Improve Reading Comprehension of The Eighth Grade Students' - Putri Lisdayanti Darwis; Mochtar Marhum; Maf'ulah Maf'ulah; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research is aimed at finding out whether the use of folktales can improve the reading comprehension of the eighth-grade students of SMP Negeri 13 Sigi. The sample was selected using the random sampling technique. The sample of this research were 54 students, which were divided into 27 students of class VIII B as an experimental group and 27 students of class VIII D as a control group. The data were collected through the reading test that consisted of pre-test and post-test. The mean score of the experimental group on the pre-test was 42 and the control group was 42. Then, the mean score of the post-test for the experimental group was 67 and the control group was 59. The data were analyzed statistically using the t-test formula with degrees of freedom Nx+Ny-2-27+27-2-52. The findings show that the t-counted value is 4.364 while the t-table value is 2.006. This means that the t-counted is higher than the t-table. Therefore, the research hypothesis is accepted. These findings answered the question from the problem formulation that the use of Folktale can improve reading comprehension of the eighth-grade students of SMP Negeri 13 Sigi. The implication of this finding is that Folktale can improve students' literacy, make learning more enjoyable, and boost their activeness and engagement in the learning process.